And again about research and educational texts - A. S. Robotova (Высшее образование в России, 2022)
This paper continues the author’s cycle devoted to the quality of research and pedagogicaltexts. These publications explore typical shortcomings and weaknesses in the texts of beginners in research and pedagogy, which impede scientific communication and research process in education sphere. The author adheres to the position that scientific text should bear subjective modality that is to express the researcher’s attitude towards the statement.